1993
DOI: 10.1107/s0108768192007547
|View full text |Cite
|
Sign up to set email alerts
|

Structural studies of cyclohexane IV

Abstract: We report an extensive neutron powder diffraction study of the high-pressure phase IV of cyclohexanediE. Using constrained Rietveld refinement we deduce approximate atomic positions for this phase which are found to be in close accord with the predictions of energy-minimization calculations. The likely relationship between the unit cell of phase IV and that of the ambient-pressure phase II is also presented. We further demonstrate, by means of an X-ray powder diffraction study of cyclohexane-hl2, that phase IV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 9 publications
4
20
0
Order By: Relevance
“…The calculated C-C bond distances in the cyclohexyl rings are in the range 1.5311-1.5329 Å, which compare favourably with experimental values for cyclohexane (1.5194-1.5275 [19] and 1.5296-1.5403 Å [20] ) and cylohexylamine hydrochloride (1.4931-1.5222 Å [21] ). The computed C-N distance (1.4660 Å) is also comparable with that determined for cylohexylamine hydrochloride (1.4873 Å [21] ).…”
Section: Structuresupporting
confidence: 65%
“…The calculated C-C bond distances in the cyclohexyl rings are in the range 1.5311-1.5329 Å, which compare favourably with experimental values for cyclohexane (1.5194-1.5275 [19] and 1.5296-1.5403 Å [20] ) and cylohexylamine hydrochloride (1.4931-1.5222 Å [21] ). The computed C-N distance (1.4660 Å) is also comparable with that determined for cylohexylamine hydrochloride (1.4873 Å [21] ).…”
Section: Structuresupporting
confidence: 65%
“…It has been reported that phase V retains structural similarities with the monoclinic phase IV [16], as also pointed out previously [12].…”
Section: Introductionsupporting
confidence: 60%
“…Prior static high pressure studies of cyclohexane [1][2][3][4][5] were performed at pressures below 3 GPa; dynamic shock wave studies were performed up to 40 GPa. The R 1 and R 2 lines of a ruby in the cyclohexane sample were well-resolved to our highest pressure, and the sample was highly transparent.…”
mentioning
confidence: 99%